Oxygen-Enhanced Atom Transfer Radical Polymerization through the Formation of a Copper Superoxido Complex - Parkatzidis, Kostas; Truong, Nghia P; Whitfield, Richard; Campi, Chiara E; Grimm-Lebsanft, Benjamin; Buchenau, Sören; Rübhausen, Michael A; Harrisson, Simon; Konkolewicz, Dominik; Schindler, Siegfried; Anastasaki, Athina (Journal of the American Chemical Society, 2023)
In controlled radical polymerization, oxygen is typically regarded as an undesirable component resulting in terminated polymer chains, deactivated catalysts, and subsequent cessation of the polymerization. Here, we report an unusual atom transfer radical polymerization whereby oxygen favors the polymerization by triggering the transformation of CuBr/L to reactive superoxido species at room temperature. Through a superoxido ARGET-ATRP mechanism, an order of magnitude faster polymerization rate and a rapid and complete initiator consumption can be achieved as opposed to when unoxidized CuBr/L was instead employed. Very high end-group fidelity has been demonstrated by mass-spectrometry and one-pot synthesis of block and multiblock copolymers while pushing the reactions to reach near-quantitative conversions in all steps. A high molecular weight polymer could also be targeted (DP = 6400) without compromising the control over the molar mass distributions ( < 1.20), even at an extremely low copper concentration (4.5 ppm). The versatility of the technique was demonstrated by the polymerization of various monomers in a controlled fashion. Notably, the efficiency of our methodology is unaffected by the purity of the starting CuBr, and even a brown highly-oxidized 15-year-old CuBr reagent enabled a rapid and controlled polymerization with a final dispersity of 1.07, thus not only reducing associated costs but also omitting the need for rigorous catalyst purification prior to polymerization.